Ferroconcrete-Like Helical Carbon Nanotube/Reduced Graphene Oxide Heterostructure 3D Networks as Sulfur Hosts for High-Performance Li-S Batteries - Luo, Zhangbin; Tao, Zengren; Li, Xinyu; Xu, Dandan; Xuan, Congxu; Wang, Zhun; Tang, Tao; Wen, Jianfeng; Li, Ming; Xiao, Jianrong (Frontiers in Energy Research, 2020)
A novel helical Carbon nanotubes (HCNT) network with a reduced graphene oxide (rGO) coating was designed and fabricated through a synergistic self-assembly and sulfuration strategy for use as an effective sulfur (S) host. A ferroconcrete frame structure with a hierarchical 3D nanostructure composed of 1D HCNT and 2D rGO nanosheets was obtained. The rGO wraps around the HCNT to form a heterostructure and provide an apparent coating that protects S. HCNT in the composite boost to create an 3D network architecture and reinforce the structural stability. Moreover, the heterostructures and rGO coatings, which are rich in wrinkles, can greatly minimize direct contact between the polysulfide and electrolyte, they also provide an abundance of active sites and boundary defects. Furthermore, the 3D interconnected structure creates effective ion diffusion channels and allows effective trapping of S and Li polysulfides. When used as a cathode, the HCNT/rGO/S cathode exhibits a high initial specific capacity of 1196 mAh g−1 at 0.1 C. The capacity decay rate of the HCNT/rGO/S is only 0.075% per cycle after cycling for 200 times at a rate of 0.1 C. This unique hybrid HCNT/rGO/S electrode design may motivate the development of other high-performance electrodes with excellent electrochemical properties.